Analysis of the atmospheric circulation pattern effects over SPEI drought index in Spain - Manzano, Antonio; Clemente, Miguel A. Morata, Ana; Luna, M. Yolanda; Beguería, Santiago; Vicente Serrano, Sergio M.; Martín, María Luisa (Atmospheric Research, 2019)
Drought episodes affect large continental areas all over the world, becoming one of the main natural hazards regarding their economic, social and environmental impacts. The design and improvement of drought monitoring and forecasting systems has become a priority application and has driven the need to a better understanding of the development of drought episodes. In this work, a study of the relationships between drought conditions over the Iberian Peninsula and teleconnection patterns with a major impact over this region is assessed. The three-month aggregated standardized precipitation evapotranspiration index (SPEI) is used to characterize different clustered areas with homogeneous hydrological behaviour on a seasonal basis. Correlation results reveal that Artic Oscillation (AO) and North Atlantic Oscillation (NAO) patterns have a significant impact on droughts in winter over large areas of the Iberian Peninsula, while the Western Mediterranean Oscillation (WeMO) pattern exhibit the largest influence on hydrological behaviour over the southeastern region. The East Atlantic (EA) pattern effects switch between weakening and reinforcement as result of a balance of two different processes such as the increase in precipitation (dominant in winter) and the increase in temperature (dominant in summer). A wavelet analysis is performed to the seasonal mean atmospheric pattern time series and clustered mean SPEI time series. The wavelet power spectra highlight common periodicity features pointing out the close relationships between the atmospheric patterns and the drought index. © 2019 Elsevier B.V. This work was been partially supported by research projects DESEMON (CGL2014-52135-C3-2-B), PCIN-2014-013-C07-04, PCIN2016-080 (UE ERA-NET Plus NEWA Project), CGL2016-78702-C2-1-R and CGL2016-78702-C2-2-R, CGL2016-81828-REDT and the ECMWF special projects (SPESMART and SPESVALE). The authors wish to thank the NOAA and Universitat de Barcelona for providing the datasets. Peer Reviewed